Fraud and Financial Markets: The 1997 Collapse of the Junior Mining Stocks - William O. Brown Jr.; Richard C.K. Burdekin (Claremont McKenna College, Department of Economics, 1999)
The Vancouver Composite Index fell by over 25% in less than six weeks during spring 1997 as the junior mining sector collapsed. We argue that this market collapse was triggered by the failure of Bre-X Minerals when that company's Indonesian claims, previously believed to contain the world's largest gold deposit, were shown to be pure fraud. Our event study, based on market returns for the Vancouver Composite Index and for a portfolio of 59 gold stocks, shows the effects of the Bre-X scandal to be both sizeable and significant. There is also some evidence that smaller exploration companies were hardest hit.
Keywords: G14; 330; Bre-X; event study; fraud; gold; mining